Effects of Microwave Modification on the Mechanical Properties of Pinus radiata Heartwood - Woyemi, Lawrence A. (Indian Forester, 2004)
Microwave modification of Pinus radiata was carried Ollt to study its influence on the mechanical properties of this species. The modification process resulted in 4.8% to 59.3% and 2.8% to 27.4% reductions in the tangential and radial MOE respectively; 5.7% to 65.5% and 0.9% to 43.5% reductions the tangential and radial MOR respectively. The reduction in the mechanical properties is due to the modification of the tracheids. The effects of changes in the conveyor belt speed are more consistent than of microwave power. The effects of both modification parameters on all the mechanical properties except the radial MOE are interdependent.